Interaction between APOE genotype and diabetes in cognitive decline. Issue 1 (6th February 2020) - Shinohara, Mitsuru; Tashiro, Yoshitaka; Suzuki, Kaoru; Fukumori, Akio; Bu, Guojun; Sato, Naoyuki
Abstract: Introduction: Although diabetes and apolipoprotein E (apoE) are both significant risk factors for dementia, including Alzheimer's disease, it remains to be clarified how they are related to each other in contributing to the risk of dementia. Methods: By reviewing the National Alzheimer's Coordinating Center (NACC) clinical records, we investigated whether diabetes affects cognitive decline depending on APOE genotype and their potential relationships with neuropathology. Results: A significant interaction between diabetes and APOE genotype exists, where diabetes affected cognitive decline in APOE3 carriers and APOE2 carriers, but not APOE4 carriers. Moreover, the presence of vascular pathology was increased by diabetes in APOE3 carriers, while APOE4 carriers nearly reached plateau levels irrespective of diabetes. Discussion: Diabetes accelerates cognitive decline, in part, through accelerating vascular impairment in non‐ APOE ε4 carriers, but such effects are negligible in APOE4 carriers, who themselves are already vulnerable to vascular impairment.